Three psychological treatments for bulimia nervosa. A comparative trial. - Fairburn, C; Jones, R; Peveler, R; Carr, S; Solomon, R; O'Connor, M; Burton, J; Hope, R (1991)
The specificity and magnitude of the effects of cognitive behavior therapy in the treatment of bulimia nervosa were evaluated. Seventy-five patients who met strict diagnostic criteria were treated with either cognitive behavior therapy, a simplified behavioral version of this treatment, or interpersonal psychotherapy. Assessment was by interview and self-report questionnaire, and many aspects of functioning were evaluated. All three treatments resulted in an improvement in the measures of the psychopathology. Cognitive behavior therapy was more effective than interpersonal psychotherapy in modifying the disturbed attitudes to shape and weight, extreme attempts to diet, and self-induced vomiting. Cognitive behavior therapy was more effective than behavior therapy in modifying the disturbed attitudes to shape and weight and extreme dieting, but it was equivalent in other respects. The findings suggest that cognitive behavior therapy, when applied to patients with bulimia nervosa, operates through mechanisms specific to this treatment and is more effective than both interpersonal psychotherapy and a simplified behavioral version of cognitive behavior therapy.